Pengaruh Kualitas Pelayanan dan Lokasi Terhadap Minat Beli Ulang dengan Kepuasan Konsumen Sebagai Variabel Mediasi pada Kopi Story UNS Surakarta - Galih Sakti Wicaksono; Retno Susanti (Teewan Journal Solutions, 2025)
Repurchase intention is an activity of purchasing more than once on a particular product where consumers do it because of satisfaction with previous purchases. Kopi Story UNS Surakarta is a place to eat that still has problems regarding consumer satisfaction which is suspected to be caused by factors of service quality and location so that it has a negative impact on consumer repurchase intention. This study aims to analyze the significance of the partial influence or mediation of service quality and location on repurchase intention with satisfaction as a mediator. The population of this study was consumers of Kopi Story UNS Surakarta with a sample size of 100 samples. The sampling technique used was purposive sampling with data collection techniques through questionnaires. The data analysis techniques used were validity test, reliability test, classical assumption test, multiple linear regression analysis with mediating variables, t test, F test, coefficient of determination test and Sobel test. The data instrument test showed that all questionnaire items were valid and reliable. The classical assumption test obtained the all research variables passed the classical assumption test. The results of the linear regression analysis obtained all variables have a positive effect on repurchase interest with the equation Y = 1.848 + 0.240X1 + 0.408X2 + 0.755Z + e. Hypothesis testing obtained partial service quality significantly influence consumer satisfaction and repurchase interest. Location partially has a significant effect on consumer satisfaction and repurchase interest. Consumer satisfaction has a significant effect on repurchase interest, and consumer satisfaction significantly mediates the effect of service quality and location on repurchase interest at Kopi Story UNS Surakarta. The F test of the model's accuracy obtained the research model used was appropriate. The determination coefficient test obtained the ability of service quality, location and consumer satisfaction in influencing repurchase interest of 82.8%.